Business Decision-Making under Uncertainty: Evidence from Employment and Number of Businesses - Vivek Ghosal; Yang Ye (Center for Economic Studies and ifo Institute (CESifo), 2013)
Using the framework provided by the asymmetric-information and real-options theories, we examine the impact of uncertainty on firms' decisions and market outcomes. We construct alternative measures of uncertainty based on survey of professional forecasters and our estimation of regression-based forecasting models for GDP growth, inflation, S&P500 stock price index, and fuel prices. Our results indicate that greater uncertainty has a negative impact on growth of employment and the number of businesses, and the effects are primarily felt by relatively smaller businesses. The impact on large businesses are generally non-existent or weaker. Our results suggest that to truly understand the effects of uncertainty on firms' decisions, we need to focus on the relatively smaller and entrepreneurial businesses. We discuss some implications for framing of policy.
Keywords: L11; D80; O30; G10; L40; 330; uncertainty; small businesses; entrepreneurship; employment; number of businesses; financing-constraints; real-options